Evaluation of neurite outgrowth stimulation and neuroprotective activities of Hericium erinaceus extracts on cell line NG 108-15 / Lai Puei-Lene - Lai, Puei-Lene (2012)
Neurotrophic factors play an indispensable role in the functionality and development of the nervous system. One of the well-studied neurotrophic factors is nerve growth factor (NGF), which is required for the growth and differentiation of dorsal root ganglion and sympathetic ganglion neurons. Studies have shown that the bioactive compounds - hericenones and erinacines of Hericium erinaceus (Bull.: Fr.) Pers., a medicinal mushroom widely used in Japan, Korea and China, can induce NGF synthesis in nerve cells. This temperate mushroom has been successfully domesticated in Malaysia and cultivated in lowland conditions. The aim of this study was to evaluate the synergistic interaction, if any, between locally grown H.erinaceus aqueous extract and commercially available NGF on neurite outgrowth stimulation activity in the neuroblastoma-glioma hybrid cell line NG108-15. The study also aimed to evaluate the neuroprotective effect of H.erinaceus aqueous extract in neuronal cells subjected to H2O2-induced oxidative stress. Aqueous extract of H.erinaceus was shown to be noncytotoxic to NG108-15 cells and human lung fibroblast MRC-5. The combination of 10 ng/mL NGF with 1 μg/mL H.erinaceus aqueous extract gave the highest percentage increase of 60.6% neurite outgrowth compared to untreated neuronal cells. The effect of neurite outgrowth stimulation was enhanced in this combined mixture when compared to the concentration of extract or NGF applied individually. The H.erinaceus extract contained neuroactive compound which induced the secretion of extracellular NGF, thereby enhancing neurite outgrowth stimulation activity. The neuritic processes stained positive for neurofilament-200 antibody indicating the extensions in the differentiated cells were of neuronal origin. On the contrary, the H.erinaceus aqueous extract failed to protect NG108-15 cells against H2O2-induced oxidative stress. There was no significant improvement in the cellular viability of NG108-15 when pre-treated with H.erinaceus extract prior to being subjected to H2O2 or when the cells were co-treated with H.erinaceus extract and H2O2. The neuroprotective effect of H.erinaceus aqueous extract was not observed even with extended hours of extract incubation in the pretreatment mode. In conclusion, the aqueous extract of locally grown H.erinaceus was not cytotoxic and contained neuroactive compounds which induced the secretion of extracellular NGF. The combined treatment of H.erinaceus extract and suboptimal concentration of NGF showed additive response in the neurite outgrowth stimulation activity of NG108-15 cells. However, the neuroprotective activity was absent in the aqueous preparation of H.erinaceus used in this study.